Performance of the Check-Direct ESBL Screen for BD MAXTM for detection of asymptomatic faecal carriage of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli and Klebsiella pneumoniae - Gröndahl-Yli-Hannuksela Kirsi; Lönnqvist Emilia; Marttila Harri; Rintala Esa; Rantakokko-Jalava Kaisu; Vuopio Jaana (Netherlands, 2022)
Objectives
Accurte diagnostic methods are crucial for the detection of extended-spectrum β-lactamase-producing Enterobacterales (ESBL-E). Besides culture-based gold-standard methods, new molecular gene detection tests are reaching the market. The aim of this study was to investigate the performance of the direct quantitative PCR (qPCR)-based methods Check-Direct ESBL and CPE Screen for BD MAXTM in relation to traditional culture-based methods for detection of ESBL-E faecal carriage.
Methods
Faecal samples were collected from healthy adult volunteers. Samples were cultured on chromogenic ESBL agar plates and were screened for ESBL-producing Escherichia coli and Klebsiella pneumoniae. Confirmed ESBL- and AmpC-producing isolates were further analysed using whole-genome sequencing. In addition, faecal samples were analysed using Check-Direct ESBL and CPE Screen for BD MAXTM and the results were compared with the gold-standard culture-based method.
Results
Of 176 faecal samples examined, 11 (6.3%) grew ESBL-producing E. coli or K. pneumoniae isolates. Among 173 analysed samples, Check-Direct ESBL Screen for BD MAXTM detected 22 (12.7%) ESBL-positive samples. No carbapenemase-producing isolates were detected. Two culture-positive samples remained negative with Check-Direct ESBL Screen for BD MAXTM. Culture-negative but qPCR-positive discrepancy was observed in 12 samples (6.9%). Altogether, concordant results were obtained for 158 samples (91.3%; 9 positive and 149 negative).
Conclusion
Check-Direct ESBL Screen for BD MAXTM is a fast screening method for ESBL carriage. However, several discrepant results were observed, which hinders interpretation. More clinical samples should be tested in combination with culture to evaluate the true benefits of this method.